2022
DOI: 10.3389/fphys.2022.968927
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory roles of the E3 ubiquitin ligase NEDD4 family in DNA damage response

Abstract: E3 ubiquitin ligases, an important part of ubiquitin proteasome system, catalyze the covalent binding of ubiquitin to target substrates, which plays a role in protein ubiquitination and regulates different biological process. DNA damage response (DDR) is induced in response to DNA damage to maintain genome integrity and stability, and this process has crucial significance to a series of cell activities such as differentiation, apoptosis, cell cycle. The NEDD4 family, belonging to HECT E3 ubiquitin ligases, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 144 publications
0
9
0
Order By: Relevance
“…NEDD4 family proteins have three functional domains: the N‐terminal C2 domain as a Ca 2+ or phospholipid‐binding motif for membrane binding, the WW domain in the central region that interacts with PPXY motifs or phospho‐serine/threonine residues in substrates, and the HECT domain in the carboxyl terminus that promotes the transfer of ubiquitin to substrates. [ 56 ] We found that NEDD4 could interact with TAK1, and the HECT domain of NEDD4 had the most binding sites for TAK1, which might be the main mechanism by which NEDD4 could reduce TAK1 protein levels by promoting K48‐linked polyubiquitination. K48‐linked polyubiquitination has been reported to negatively regulate the activation of TAK1; for example, FBXW2 degrades TAK1 via targeting TAK1 for K48‐linked polyubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4 family proteins have three functional domains: the N‐terminal C2 domain as a Ca 2+ or phospholipid‐binding motif for membrane binding, the WW domain in the central region that interacts with PPXY motifs or phospho‐serine/threonine residues in substrates, and the HECT domain in the carboxyl terminus that promotes the transfer of ubiquitin to substrates. [ 56 ] We found that NEDD4 could interact with TAK1, and the HECT domain of NEDD4 had the most binding sites for TAK1, which might be the main mechanism by which NEDD4 could reduce TAK1 protein levels by promoting K48‐linked polyubiquitination. K48‐linked polyubiquitination has been reported to negatively regulate the activation of TAK1; for example, FBXW2 degrades TAK1 via targeting TAK1 for K48‐linked polyubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only MG132 was unable to rescue RNA Pol II from degradation in KSHV-positive BCBL1 cells. Previously, it has been reported that RNA polymerase II ubiquitylation and degradation are important DNA damage responses, conserved from yeast to humans ( 51 ), and identified NEDD4 as the prime E3 ubiquitin ligase that polyubiquitinylates RNA Pol II, leading to its degradation ( 52 ). To determine the role of NEDD4, we knocked down NEDD4 and noticed that RNA Pol II degradation was reversed even in the absence of KSHV during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…WWP2, encoded by the WWP2 gene, is expressed in several tissues/organs throughout the human body and regulates several cellular, physiological and pathological processes [ 29 , 30 ]. WWP2 was associated with oxidative stress-mediated VSMC injury in different cardiovascular diseases, such as AS, ischemia-reperfusion injury, cardiomyopathy and heart failure [ 31 , 32 ], suggested that WWP2 could be a significant target for treating several cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%